Innovations for Sustainable Building Design and Refurbishment in Scotland The Outputs of CIC Start Online Project - Dimitrijević, Branka (Green Energy and Technology,, 2013)
This book presents innovations for sustainable building design and refurbishment developed and tested through feasibility studies undertaken by researchers at Scottish universities in collaboration with small to medium size enterprises in Scotland during the 'CIC Start Online' project that ran from September 2009 to February 2013. The project was led by Glasgow Caledonian University in collaboration with Edinburgh Napier University, Glasgow School of Art, Heriot-Watt University, the Robert Gordon University, University of Edinburgh and the University of Strathclyde Glasgow. The book includes chapters on Context and Policies, Planning, Building Design, Technologies, Construction, Refurbishment and Performance. The contents of each chapter are based on 63 completed studies that were initiated by businesses operating in the construction sector or providing services to the sector, indicating the scope of research required to assist the industry to develop more sustainable products and processes. The book informs the reader about the range of innovations that were tested and highlight potential future research areas. Readers can find in-depth information by accessing the project website www.cicstart.org, where full reports on most studies and the video recordings of interactive online seminars that presented the outcomes of the studies are available.  Along with the new knowledge on how innovations for sustainable building design and refurbishment can be applied in practice, the book demonstrates how joint projects of several universities can be successfully managed and how an immediate knowledge transfer can be organized by using web tools to reach over 2,200 current members nationally and internationally (in UK and 53 other countries).